2014
DOI: 10.1016/j.placenta.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-7 acts as an adhesion molecule during implantation and increased expression is associated with miscarriage

Abstract: Galectin-7 is produced by endometrial epithelium and is abnormally elevated in the endometrium of women with a history of miscarriage. Serum levels may be useful as a predictive biomarker of miscarriage. Our data suggests that galectin-7 facilitates adhesion of the embryo to the endometrium and elevated galectin-7 may result in abnormal adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
0
29
1
1
Order By: Relevance
“…To mimic the rising levels of galectin-7 determined in EC, EC cell lines were treated with recombinant galectin-7 for the in vitro functional assays. The concentration used (1 µg/ml) was determined from the manufacturer's protocols and dose-response trials in previous studies (14,15), but it is notable that extracellular galectin-7 remains to be identified in EC. Galectin-7 could not be detected in the endometrial epithelial EC cell line conditioned media (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To mimic the rising levels of galectin-7 determined in EC, EC cell lines were treated with recombinant galectin-7 for the in vitro functional assays. The concentration used (1 µg/ml) was determined from the manufacturer's protocols and dose-response trials in previous studies (14,15), but it is notable that extracellular galectin-7 remains to be identified in EC. Galectin-7 could not be detected in the endometrial epithelial EC cell line conditioned media (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…no. ELH-Galectin7-001; RayBiotech, Inc., Norcross, GA, USA), according to the manufacturer's protocols (15,23). For the cell lines, cells were cultured in serum-free media for 48 h prior to cell lysate being collected for the ELISA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found in female reproductive system (35) and its expression changes in some cancers of the reproductive tract, including that of the ovary and uterus. Endometrial epithelium can produce galectin-7 and women with a history of miscarriage have abnormally elevated levels of galectin-7 in the endometrium (42). GalNAc-T6 is one of the members of the UDP-N-acetylalpha-D-galactosamine: polypeptide N-acetylgalactosaminyltransferase family of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated galectin-7 expression is associated with uterine repair after menstruation (Evans et al 2014 ), miscarriage (Menkhorst et al 2014b ), and preeclampsia (Menkhorst et al 2014a ). Many of these observations relate to the proposed role for galectin-7 in reepithelialization associated with wound repair (Panjwani 2014 ).…”
Section: Galectinsmentioning
confidence: 99%